2012
DOI: 10.3174/ajnr.a3330
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Integrity of Cerebral Fiber Tracts in Hereditary Spastic Paraparesis withSPG11Mutation

Abstract: BACKGROUND AND PURPOSE: ARHSP-TCC is characterized by progressive leg spasticity, ataxia, and cognitive dysfunction. Although mutations in the human SPG11 gene were identified as responsible for ARHSP-TCC, the cerebral fiber integrity has not been assessed systemically. The objective of this study was to assess cerebral fiber integrity and its clinical significance in patients with ARHSP-TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
5
8
0
Order By: Relevance
“…The main weakness of this study is the small number of patients with any one of the specific gene variantsthe largest group being the 11 patients with SPG4 mutation. However, this reflects the rarity of these conditions, and it is in line with previous neuroimaging studies in these patients (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, this is a cross-sectional study, involving patients with a relatively long disease duration.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The main weakness of this study is the small number of patients with any one of the specific gene variantsthe largest group being the 11 patients with SPG4 mutation. However, this reflects the rarity of these conditions, and it is in line with previous neuroimaging studies in these patients (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, this is a cross-sectional study, involving patients with a relatively long disease duration.…”
Section: Discussionsupporting
confidence: 66%
“…All these aspects combined together In our study we found that, on the basis of DT MR imaging, patients with pHSP and cHSP harbor severe damage to the motor WM, including the body of the CC, WM areas underneath the primary motor and premotor cortices, and cerebral peduncles. This pattern was previously reported in a study of 24 cases with and without gene identification (16), as well as in small case series of patients carrying SPG11 (8)(9)(10)(11)(12), SPG4 (13), and SPG7 (14,15) mutations. Apart from patients with SPG11, who showed global brain atrophy and CC thinning, in the other HSP cases, DT MR imaging was able to demonstrate microstructural WM abnormalities in the absence of macroscopically detectable brain atrophy.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Rezende and colleagues also demonstrated the absence of cortical thinning as a hallmark of this pure subtype of HSP 44,45 . Regarding HSP-SPG11, both França et al 46 and Pan et al 47 revealed widespread white matter microstructural disruption. Pan et al also demonstrated a distal-proximal gradient, whereas França et al identified major deep grey matter volumetric loss 46,47 .…”
mentioning
confidence: 99%
“…Regarding HSP-SPG11, both França et al 46 and Pan et al 47 revealed widespread white matter microstructural disruption. Pan et al also demonstrated a distal-proximal gradient, whereas França et al identified major deep grey matter volumetric loss 46,47 .…”
mentioning
confidence: 99%